1988
DOI: 10.1161/01.res.63.2.415
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular effects of atrial natriuretic factor: interaction with alpha 1- and alpha 2-adrenoceptors.

Abstract: The cremaster skeletal muscle of anesthetized rats was denervated and extended with intact circulation into a tissue bath. Intravital microscopy was used to measure microvessel diameter at three different anatomical levels within the microcirculation: large distributing arterioles (x control diameter = 100 +/- 7 micron), large capacitance venules (147 +/- 8 micron), and small terminal arterioles (17 +/- 1 micron). Norepinephrine (NE) was added to the cremaster bath to produce intermediate reductions in diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1989
1989
1996
1996

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 56 publications
1
11
1
Order By: Relevance
“…In vivo studies with selective a r and a 2-agonists have sup ported the concept of heterogeneity of postjunc tional a-adrenoceptors in human vasculature. Faber and colleagues demonstrated that A N F was highly potent in selectively reversing a r adrenoceptormediated constriction (13), but in their study a 2-adrenoceptor-m ediated constriction was ANF in sensitive, which may explain the absence of an ef fect of A N F on cold-induced vasoconstriction in our study. Our experiments with postocclusive re active hyperem ia indicate that A N F apparently does not modulate microvascular vasodilator func tion.…”
Section: A J W Branten Et Alcontrasting
confidence: 66%
“…In vivo studies with selective a r and a 2-agonists have sup ported the concept of heterogeneity of postjunc tional a-adrenoceptors in human vasculature. Faber and colleagues demonstrated that A N F was highly potent in selectively reversing a r adrenoceptormediated constriction (13), but in their study a 2-adrenoceptor-m ediated constriction was ANF in sensitive, which may explain the absence of an ef fect of A N F on cold-induced vasoconstriction in our study. Our experiments with postocclusive re active hyperem ia indicate that A N F apparently does not modulate microvascular vasodilator func tion.…”
Section: A J W Branten Et Alcontrasting
confidence: 66%
“…Rather, they found that ANP increased the vascular resistance to venous return, indicative of vascular constriction instead of dilation. Recently, Faber et al (22), using denervated skeletal muscle in microscopic observation, reported that ANP increased diameters of the large distributing arterioles and capacitance venules preconstricted by a-1 agonist, and also dilated the intact small terminal arterioles. In general, vascular constriction causes an increase of blood pressure, even if only transiently; this was not seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Sarelius & Huxley (1990) have shown that ANP can produce vasodilatation of terminal arterioles in the hamster cheek pouch. However, other investigators have found in the rat that terminal arterioles do not respond (Proctor & Bealer, 1987) or only minimally to topically applied ANP (Faber et al, 1988). Accordingly, in this study, we examined the effect of ANP on the diameter of skeletal vessels.…”
Section: Introductionmentioning
confidence: 90%